Adoption of corporate social responsibility: empirical evidence from Malaysian SMEs - Thamil Durai Chelliah,; Mathivannan Jaganathan,; Mahendra Kumar Chelliah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In the new global economy, corporate social responsibility has become a central issue of most of the government but a number of cases of business owners being socially irresponsible are dramatically increasing. Therefore, this study has thoroughly examined most contributing factor of corporate social responsibility adoption among SMEs. It is undeniable, that the contributions of SMEs toward the corporate social responsibility are increasing in the society along with the number of SMEs gradually increase in the market and play a significant role in the corporate social responsibility to improve the economic and social development of the nation. The purpose of this research is to examine further in-depth the relevant factors that influence the managers of SMEs in the adoption of corporate social responsibility practices. Quantitative data were collected using the self-administered questionnaire that was distributed to a sample of 384 respondents. In this study, Pearson Correlation Analysis and Multiple Linear Regressions were used to test the importance of all of the four independent variables which are profit maximization, philanthropy responsibility, external pressure, and moral responsibility. The results indicated that all of the tested motivational factors that influence adoption of corporate social responsibility have significant association with corporate social responsibility of SMEs. Therefore, it can be concluded that the result may provide some insight to business leaders with more practical perspectives about motivational factors of corporate social responsibility in Malaysia.